Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

Hormonal regulation of metabolic and reproductive homeostasis in transition dairy cows: Current insights and future perspectives - Rano Dwijaya Sarno; Khalid A. Abdoun; Mohammed A. Al-Badwi; Emad M. Samara; Ahmed A. Al-Haidary (Animal Reproduction Science, 2026)

Ontogeny of the esophagus in quail embryos: Morphological, histochemical and ultrastructural changes - Samara M. Ali; Salma A. Mohamed; Mohamed A.A. Mahdy; Fatma A. Madkour (Tissue and Cell, 2026)

Degradability, Phytotoxicity, and Life Cycle Assessment of Chestnut Waste Biocomposites - Simão B. Silva; Samara Rodrigues; Elena Surra; Elsa Vieira; Cristina Delerue-Matos; Olga M. Freitas; Valentina F. Domingues (Environmental Processes, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Assessment of space weather modeling capabilities and transition to operations - Maria M. Kuznetsova; Martin A. Reiss; Edmund Henley; Eric Adamson; Suzy Bingham; Mario M. Bisi; François-Xavier Bocquet; Laura Boucheron; Min-Yang Chou; Claudio Corti; Gian Luca Delzanno; Richard A. Fallows; et al. (Advances in Space Research, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Effects of model misspecification and data availability on spatially-explicit assessment model performance - Samara Nehemiah; Amy M. Schueller; Michael J. Wilberg (Fisheries Research, 2025)

Histological alterations in placentas of normal and anomalous pups: correlation with neonatal outcomes and fetal health - Laura M. Lovo; Marina Vilela Estevam; Samara Beretta; Amanda Marmol; Loren M. Pasqui; Fernanda A. Rodrigues-Silva; Renata O. Barreto; Alessandre Hataka; Gilson Hélio Toniollo; Maria Lúcia G. Lourenço; Maricy Apparício (Theriogenology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Assessing the link between skin Aquaporins and morphological attributes under simulated heat stress conditions: A comparative investigation between hair and wool sheep breeds - Emad M. Samara; Majdi A. Bahadi; Muhammed A. Khan; Muhammed Afzal; Mohammed A. Al-Badwi; Khalid A. Abdoun; Salem S. Alghamdi; Ahmed A. Al-Haidary (Journal of Thermal Biology, 2025)

Long‐haul flights and migratory routes of a nectar‐feeding bat - Theresa M. Laverty; Debbie C. Buecher; David C. Dalton; Mallory L. Davies; Fernando Gual‐Suárez; Paul A. Heady; Rodrigo A. Medellín; Mayra C. Ordóñez‐García; Samara Pérez‐Harp; A. Nayelli Rivera‐Villanueva; Brandi D. Stevenson; Kathryn E. Stoner; et al. (Ecology, 2025)

Spirulina (Arthrospira platensis) immobilization in calcium-alginate beads can provide a way to produce food-grade C-phycocyanin following a biorefinery perspective - Samara C. Silva-Pituco; Leandro L. Aquino; Madalena M. Dias; M. Filomena Barreiro (Algal Research, 2025)

eDNA metabarcoding detection of nearshore juvenile white sharks (Carcharodon carcharias) and prey fish communities - Zachariah S. Merson; Elizabeth E. Jahn; Matthew A. Barnes; Emily A. Spurgeon; Patrick T. Rex; Jack T. Elstner; Yamilla N. Samara Chacon; James M. Anderson; Whitney D. Jones; Christopher G. Lowe (Journal of Experimental Marine Biology and Ecology, 2025)

The interrelationship between macrominerals and heat stress in ruminants: current perspectives and future directions - a review - Emad M. Samara; Mohammed A. Al-Badwi; Khalid A. Abdoun; Mutassim M. Abdelrahman; Aly B. Okab; Majdi A. Bahadi; Ahmed A. Al-Haidary (Veterinary Research Communications, 2025)

A Systematic Review and Meta-Analysis Assessing the Impact of Improved Cookstove Technology Trials (ICTs) on Household Air Pollution and Human Health in Sub-Saharan Africa - David Dillon; Samara Reigh; Kristen M. Rappazzo; Thomas J. Luben; Anne M. Weaver (Current Environmental Health Reports, 2025)
Purpose of Review A major contributor to household air pollution (HAP) in sub-Saharan Africa (SSA) is unclean cooking fuel. Improved cookstove technology (ICT) interventions have been promoted as a solution, but their impacts on health are unclear. Our aim is to conduct a systematic review to explore the impacts of ICT interventions on health outcomes in SSA. We conducted a systematic review, following PRISMA guidelines, on ICT interventions in SSA from 2000-present. We performed this search in MEDLINE, PubMed, Web of Science, Web of Science CABI, and EMBASE via ProQuest. Two reviewers assessed each study using predefined inclusion/exclusion criteria and extracted data. We evaluated each study on participant selection, exposure assessment, control comparability, outcomes, analyses, and biases. Recent Findings From 4,461 articles, k = 23 ( n = 31,261 individuals) articles described results of ICT interventions on health outcomes. Pooled mean exposure estimates for fine particulate matter (PM 2.5 ) in control and intervention groups were 102.88 µg/m 3 (95% confidence interval [CI]I: 52.63, 153.14; I 2 96.9%) and 101.76 µg/m 3 (95%CI: 57.47, 146.06; I 2 98.2%), respectively. Estimates for pooled mean carbon monoxide (CO) were 2.40 ppm (95% CI: 0, 8.33; I 2 99.0%) and 1.66 ppm (0, 4.91; I 2 98.5%) respectively. Of health outcomes, 19.4% were reported as significantly different between control and intervention groups. Summary There is mixed evidence that ICT interventions influence health outcomes due to heterogeneity in study designs, sample size, stove stacking, etc. ICT interventions may decrease HAP, but other sources of air pollutant exposure are not addressed by improved cookstoves.

Hyperkeratotic gastritis in two-toed sloths (Choloepus didactylus) from wildlife rescue - Washington A. Pereira; David F. Conga; Antônio M. Costa; Adriana C. Jaques; Alexsandro P. Damasceno; Samara C. Loura; Pedro H. Portela; Andressa B. Menezes; Ana S. Ribeiro (Journal of Comparative Pathology, 2024)

Profiling the dynamic variations in body and scrotal surface temperatures of goats reared under stressful conditions using infrared thermography: Analytical perspectives - Emad M. Samara (Journal of Thermal Biology, 2024)

Confirmation that Monochamol is a Male Produced Aggregation-Sex Pheromone for Monochamus maculosus Haldeman (Coleoptera: Cerambycidae) - Samara M. M. Andrade; Quentin Guignard; Sandy M. Smith; Jeremy D. Allison (Journal of Chemical Ecology, 2024)

Climatic niche evolution and speciation modes in the transisthmian Alpheus shrimps (Caridea: Alpheidae) - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Samara de P. de Barros‐Alves; Ariádine Cristine de Almeida; Marco Aurélio Mendes Elias; Carla Hurt; Kristin M. Hultgren (Journal of Biogeography, 2024)
Aim We studied the niche evolution and diversification modes in transisthmian Alpheus shrimps by examining the interplay between environmental niche divergence and conservatism in allopatric sister species. In a broader perspective, the current study analysed the evolution of climatic niche and the role of the environment in species diversification of Alpheus transisthmian shrimp. Location Atlantic and Eastern‐Pacific oceans. Taxon Alpheus shrimps (Caridea: Alpheidae). Methods We assembled georeferenced occurrences for 33 species of Alpheus (with 24 sister species) from a time‐calibrated molecular phylogeny. We modelled their ecological niches and assessed niche overlap through pairwise comparisons. Additionally, we performed phylogenetic reconstructions of the ancestral environmental niche, for each niche axis. Results Our results demonstrate that thermal tolerances, food availability and hydrodynamic forces were relevant environmental axes in evolutionary processes in transisthmian species of Alpheus . Among the 528 paired comparisons, we found that most niches were divergent, including in 12 clades formed by pairs of sister species (in only two of these clades were the niches fully equivalent). Phylogenetic reconstructions of ancestral niches showed an initial niche conservatism in all axes, with divergences intensifying in the last 12 million years. Main Conclusions We found evidence that confirms the relevance of the environmental changes that occurred in the West Atlantic and East Pacific for niche evolution in transisthmian Alpheus species, as well as for the emergence of some lineages. Our findings provide evidence for different modes of Alpheus species speciation in a period consistent with the closure of the Isthmus of Panama.

Comparison between commercial media and TRIS-egg yolk extender in the refrigerated storage of collared peccary semen at 17 °C - Romário P. Santos; Samara S.J. Moreira; Luana G.P. Bezerra; Yasmim C.S. Cavalcante; Ana G. Pereira; Tayná M. Matos; Moacir F. Oliveira; Alexandre R. Silva (Animal Reproduction Science, 2024)

Allometric models for non-destructive estimation of the leaflet area in acai (Euterpe oleracea Mart.) - Samara K. A. de Sousa; Rodrigo G. M. Nascimento; Flavio Henrique S. Rodrigues; Rafael G. Viana; Lucas C. da Costa; Hugo A. Pinheiro (Trees, 2024)

Applicability of thermography as a potential non-invasive technique to assess the body-thermal status of heat-stressed and water-deprived goats (Capra hircus) - Emad M. Samara; Mohammed A. Al-Badwi; Khalid A. Abdoun; Ahmed A. Al-Haidary (Journal of Thermal Biology, 2024)

Effects of different subcutaneous sites on heterotopic autotransplantation of canine ovarian tissue - Fabiana AS Brandão; Danielle CC de Brito; Leda MC Pereira; Kele A Alves; Lucy VS Ñaupas; Samara S de Souza; Duanny M de S Cunha; Reginaldo P de S Filho; Benner G Alves; Ana PR Rodrigues; Dárcio IA Teixeira (Veterinary Research Communications, 2023)

Can Pheromones Contribute to Phylogenetic Hypotheses? A Case Study of Chrysomelidae - Aluska T. dos Santos; João P. A. Souza; Isaac R. Jorge; Samara M. M. Andrade; Brunno B. Rosa; Maurício O. Moura; Paulo H. G. Zarbin (Journal of Chemical Ecology, 2023)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

Volatile organic compounds emitted by conventional and “green” cleaning products in the U.S. market - Alexis M. Temkin; Samara L. Geller; Sydney A. Swanson; Nneka S. Leiba; Olga V. Naidenko; David Q. Andrews (Chemosphere, 2023)

The variable influence of anthropogenic noise on summer season coastal underwater soundscapes near a port and marine reserve - Samara M. Haver; Joseph Haxel; Robert P. Dziak; Lauren Roche; Haru Matsumoto; Christa Hvidsten; Leigh G. Torres (Marine Pollution Bulletin, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Cytotoxicity and performance of Pectin/ Ferric vanadate oxide/ Cetyltrimethylammonium Bromide foaming nano-system for drilling sustainable geothermal wells - Amany A. Aboulrous; Philip Jaeger; Hanin Samara; Martina Szabries; Héctor Cano Esteban; Maria Romero Lopez; Juan A. de Isabel; Eman M. Mostafa (Geothermics, 2023)

Microbial meat: A sustainable vegan protein source produced from agri-waste to feed the world - Samara Cardoso Alves; Erick Díaz-Ruiz; Bruna Lisboa; Minaxi Sharma; Solange I. Mussatto; Vijay Kumar Thakur; Deepak M. Kalaskar; Vijai Kumar Gupta; Anuj K. Chandel (Food Research International, 2023)

Oxidative potential of ambient PM2.5 from São Paulo, Brazil: Variations, associations with chemical components and source apportionment - Eleni Serafeim; Athanasios Besis; Athanasios Kouras; Camila N. Farias; Aleinnys B. Yera; Guilherme M. Pereira; Constantini Samara; Pérola de Castro Vasconcellos (Atmospheric Environment, 2023)

A micromechanical based finite element model approach to accurately predict the effective thermal properties of micro-aerated chocolate - D. Bikos; G. Samaras; M.N. Charalambides; P. Cann; M. Masen; C. Hartmann; J. Vieira; A. Sergis; Y. Hardalupas (Innovative Food Science & Emerging Technologies, 2023)

Highly effective adsorption of caffeine by a novel activated carbon prepared from coconut leaf - Elvio N. Oliveira; Alex T. Meneses; Samara F. de Melo; Franciele M. R. Dias; Maisa T. B. Perazzini; Hugo Perazzini; Lucas Meili; João I. Soletti; Sandra H. V. Carvalho; Mozart D. Bispo (Environmental Science and Pollution Research, 2022)

Corrigendum: Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2022)

Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2021)
Chronic low-frequency noise from commercial shipping is a worldwide threat to marine animals that rely on sound for essential life functions. Although the U.S. National Oceanic and Atmospheric Administration recognizes the potential negative impacts of shipping noise in marine environments, there are currently no standard metrics to monitor and quantify shipping noise in U.S. marine waters. However, one-third octave band acoustic measurements centered at 63 and 125 Hz are used as international (European Union Marine Strategy Framework Directive) indicators for underwater ambient noise levels driven by shipping activity. We apply these metrics to passive acoustic monitoring data collected over 20 months in 2016–2017 at five dispersed sites throughout the U.S. Exclusive Economic Zone: Alaskan Arctic, Hawaii, Gulf of Mexico, Northeast Canyons and Seamounts Marine National Monument (Northwest Atlantic), and Cordell Bank National Marine Sanctuary (Northeast Pacific). To verify the relationship between shipping activity and underwater sound levels, vessel movement data from the Automatic Identification System (AIS) were paired to each passive acoustic monitoring site. Daily average sound levels were consistently near to or higher than 100 dB re 1 μPa in both the 63 and 125 Hz one-third octave bands at sites with high levels of shipping traffic (Gulf of Mexico, Northeast Canyons and Seamounts, and Cordell Bank). Where cargo vessels were less common (the Arctic and Hawaii), daily average sound levels were comparatively lower. Specifically, sound levels were ∼20 dB lower year-round in Hawaii and ∼10-20 dB lower in the Alaskan Arctic, depending on the season. Although these band-level measurements can only generally facilitate differentiation of sound sources, these results demonstrate that international acoustic indicators of commercial shipping can be applied to data collected in U.S. waters as a unified metric to approximate the influence of shipping as a driver of ambient noise levels, provide critical information to managers and policy makers about the status of marine environments, and to identify places and times for more detailed investigation regarding environmental impacts.

A Roadmap for Policy-Relevant Sea-Level Rise Research in the United Arab Emirates - Hannah Melville-Rea; Clare Eayrs; Nasser Anwahi; John A. Burt; Denise Holland; Fatin Samara; Francesco Paparella; Ahmed Hassan Al Murshidi; Maryam Rashed Al-Shehhi; David M. Holland (Frontiers in Marine Science, 2021)
The United Arab Emirates (UAE) has a long-term policy horizon, the financial capital, and a vision for a sustainable knowledge-based economy. These characteristics uniquely situate it as a potential leader for sea-level rise research. Climate science is already growing, and at the center of the UAE's pivot toward climate research is a burgeoning concern for sea-level rise. Over 85% of the UAE's population and more than 90% of the nation's infrastructure is within a few meters of present-day sea-level. With its low-lying and shallow-sloping geography (about 35 cm per km), this high-value coastline, including the rapidly expanding cities of Dubai and Abu Dhabi, is particularly vulnerable to sea-level rise. Meanwhile, limited regional research and data scarcity create deep uncertainty for sea-level projections. We set out a potential roadmap for the UAE to capitalize on its strengths to create usable and relevant sea-level projections for the region. With a newly established Climate Change Research Network, the UAE government is beginning to draw together universities and research centers for “furthering effective data collection and management, and advancing policy-relevant research on climate impacts and adaptation 1 .” By consolidating ideas from the science community within the UAE, we identify promoters and barriers to data gathering, information sharing, science-policy communication, and funding access. Our paper proposes pathways forward for the UAE to integrate sea-level science with coastal development and form best practices that can be scaled across climate science and throughout the region.

The Next Wave of Passive Acoustic Data Management: How Centralized Access Can Enhance Science - Carrie C. Wall; Samara M. Haver; Leila T. Hatch; Jennifer Miksis-Olds; Rob Bochenek; Robert P. Dziak; Jason Gedamke (Frontiers in Marine Science, 2021)
Passive acoustic data collection has grown exponentially over the past decade resulting in petabytes of data that document our ocean soundscapes. This effort has resulted in two big data challenges: (1) the curation, management, and global dissemination of passive acoustic datasets and (2) efficiently extracting critical information and comparing it to other datasets in the context of ecosystem-based research and management. To address the former, the NOAA National Centers for Environmental Information recently established an archive for passive acoustic data. This fast-growing archive currently contains over 100 TB of passive acoustic audio files mainly collected from stationary recorders throughout waters in the United States. These datasets are documented with standards-based metadata and are freely available to the public. To begin to address the latter, through standardized processing and centralized stewardship and access, we provide a previously unattainable comparison of first order sound level-patterns from archived data collected across three distinctly separate long-term passive acoustic monitoring (PAM) efforts conducted at regional and national scales: NOAA/National Park Service Ocean Noise Reference Station Network, the Atlantic Deepwater Ecosystem Observatory Network, and the Sanctuary Soundscape Monitoring Project. Nine sites were selected from these projects covering the Alaskan Arctic, Northeast and Central Pacific, Gulf of Mexico, Caribbean Sea, and Mid and Northwest Atlantic. Sites could generally be categorized into those strongly influenced by anthropogenic noise (e.g., vessel traffic) and those that were not. Higher sound levels, specifically for lower frequencies (<125 Hz), and proximity to densely populated coastal zones were common characteristics of sites influenced by anthropogenic noise. Conversely, sites with lower overall sound levels and away from dense populations resulted in soundscape patterns influenced by biological sources. Seasonal variability in sound levels across selected decidecade bands was apparent for most sites and often represented changes in the presence or behavior of sound-producing species. This first order examination of levels across projects highlights the utility of these initial metrics to identify patterns that can then be examined in more detail. Finally, to help the PAM community collectively and collaboratively move forward, we propose the next frontier for scalable data stewardship, access, and processing flow.

Using chrono-physiological management in form of shifting the feeding time has no advantage in goat kids exposed to experimentally induced heat stress - Mohammed A. Al-Badwi; Emad M. Samara; Khalid A. Abdoun; Ahmed A. Al-Haidary (Tropical Animal Health and Production, 2021)

Plant volatiles induced by Duponchelia fovealis (Lepidoptera: Crambidae) in two cultivars of strawberry and its attraction to the predator Podisus nigrispinus (Hemiptera: Pentatomidae) - Delia M. Pinto-Zevallos; Camila B. C. Martins; Samara M. M. Andrade; Maria A. Zawadneak; Paulo H. G. Zarbin (Arthropod-Plant Interactions, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Fortnightly variability of total suspended solids and bottom sediments in a macrotidal estuarine complex on the Brazilian northern coast - Jefferson H. F. Serejo; Thays T. L. Santos; Hugo P. Lima; Igor H. R. Azevedo; Vinicius H. M. Dos Santos; Samara A. Eschrique (Journal of Sedimentary Environments, 2020)

The effect of modeling choices on updating intensity-duration-frequency curves and stormwater infrastructure designs for climate change - Lauren M. Cook; Seth McGinnis; Constantine Samaras (Climatic Change, 2020)
Intensity-duration-frequency (IDF) curves, commonly used in stormwater infrastructure design to represent characteristics of extreme rainfall, are gradually being updated to reflect expected changes in rainfall under climate change. The modeling choices used for updating lead to large uncertainties; however, it is unclear how much these uncertainties affect the design and cost of stormwater systems. This study investigates how the choice of spatial resolution of the regional climate model (RCM) ensemble and the spatial adjustment technique affect climate-corrected IDF curves and resulting stormwater infrastructure designs in 34 US cities for the period 2020 to 2099. In most cities, IDF values are significantly different between three spatial adjustment techniques and two RCM spatial resolutions. These differences have the potential to alter the size of stormwater systems designed using these choices and affect the results of climate impact modeling more broadly. The largest change in the engineering decision results when the design storm is selected from the upper bounds of the uncertainty distribution of the IDF curve, which changes the stormwater pipe design size by five increments in some cases, nearly doubling the cost. State and local agencies can help reduce some of this variability by setting guidelines, such as avoiding the use of the upper bound of the future uncertainty range as a design storm and instead accounting for uncertainty by tracking infrastructure performance over time and preparing for adaptation using a resilience plan.

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Comparing the Underwater Soundscapes of Four U.S. National Parks and Marine Sanctuaries - Samara M. Haver; Michelle E. H. Fournet; Robert P. Dziak; Christine Gabriele; Jason Gedamke; Leila T. Hatch; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Sofie M. Van Parijs (Frontiers in Marine Science, 2019)

Male yellow-crowned bishops (Euplectes afer afer) acquire a novel foraging behaviour by social learning - Samara Danel; Magdalena van Buuren; Auguste M. P. von Bayern; François Osiurak (Journal of Ethology, 2019)

Short-term heat shock proteins 70 and 90 mRNA expression profile and its relation to thermo-physiological parameters in goats exposed to heat stress - M. F. El-Zarei; A. M. Alseaf; A. A. Alhaidary; E. F. Mousa; A. B. Okab; E. M. Samara; K. A. Abdoun (International Journal of Biometeorology, 2019)

Mate Recognition by the Green Mate Borer, Hedypathes betulinus (Coleoptera: Cerambycidae): the Role of Cuticular Compounds - Samara M. M. Andrade; Daiane Szczerbowski; Diogo Montes Vidal; Jeremy D. Allison; Paulo H. G. Zarbin (Journal of Insect Behavior, 2019)

Integrating multidisciplinary instruments for assessing coastal vulnerability to erosion and sea level rise: lessons and challenges from the Adriatic Sea, Italy - D. Bonaldo; F. Antonioli; R. Archetti; A. Bezzi; A. Correggiari; S. Davolio; G. De Falco; M. Fantini; G. Fontolan; S. Furlani; M. G. Gaeta; G. Leoni; et al. (Journal of Coastal Conservation, 2019)

Ground-hornbills (Bucorvus) show means-end understanding in a horizontal two-string discrimination task - Samara Danel; Auguste M. P. von Bayern; François Osiurak (Journal of Ethology, 2019)

Protective role of jaboticaba Plinia peruviana peel extract in copper-induced cytotoxicity in Allium cepa - Francini Franscescon; Samara C. Mazon; Kanandra T. Bertoncello; Aline A. Boligon; Adrieli Sachett; Cassiano L. Rambo; Denis B. Rosemberg; Jacir Dal Magro; Anna M. Siebel (Environmental Science and Pollution Research, 2018)

Smad4 and epithelial–mesenchymal transition proteins in colorectal carcinoma: an immunohistochemical study - M. Ioannou; E. Kouvaras; R. Papamichali; M. Samara; I. Chiotoglou; G. Koukoulis (Journal of Molecular Histology, 2018)

Influence of dietary chromium yeast supplementation on apparent trace elements metabolism in growing camel (Camelus dromedarius) reared under hot summer conditions - Ibrahim A. Alhidary; M. A. Alsofi; K. A. Abdoun; E. M. Samara; A. B. Okab; A. A. Al-Haidary (Tropical Animal Health and Production, 2018)

Human orbital and anterior medial prefrontal cortex: Intrinsic connectivity parcellation and functional organization - Zoe Samara; Elisabeth A. T. Evers; Alexandros Goulas; Harry B. M. Uylings; Grazyna Rajkowska; Johannes G. Ramaekers; Peter Stiers (Brain Structure and Function, 2017)

Effects of omega-3 on matrix metalloproteinase-9, myoblast transplantation and satellite cell activation in dystrophin-deficient muscle fibers - Samara Camaçari de Carvalho; Sajedah M. Hindi; Ashok Kumar; Maria Julia Marques (Cell and Tissue Research, 2017)

Run, hide, or fight: anti-predation strategies in endangered red-nosed cuxiú (Chiropotes albinasus, Pitheciidae) in southeastern Amazonia - Adrian A. Barnett; João M. Silla; Tadeu de Oliveira; Sarah A. Boyle; Bruna M. Bezerra; Wilson R. Spironello; Eleonore Z. F. Setz; Rafaela F. Soares da Silva; Samara de Albuquerque Teixeira; Lucy M. Todd; Liliam P. Pinto (Primates, 2017)

Adaptive strategies of two Mediterranean grapevines varieties (Aragonez syn. Tempranillo and Trincadeira) face drought: physiological and structural responses - M. Vaz; R. Coelho; A. Rato; R. Samara-Lima; L. L. Silva; E. Campostrini; J. B. Mota (Theoretical and Experimental Plant Physiology, 2016)

Factors controlling nitrous oxide emissions from a full-scale activated sludge system in the tropics - Ariane C. Brotto; Débora C. Kligerman; Samara A. Andrade; Renato P. Ribeiro; Jaime L. M. Oliveira; Kartik Chandran; William Z. de Mello (Environmental Science and Pollution Research, 2015)

Diffuse Helium and Hydrogen Degassing to Reveal Hidden Geothermal Resources in Oceanic Volcanic Islands: The Canarian Archipelago Case Study - Fátima Rodríguez; Nemesio M. Pérez; Eleazar Padrón; Gladys Melián; Pedro A. Hernández; María Asensio-Ramos; Samara Dionis; Gabriel López; Rayco Marrero; Germán D. Padilla; José Barrancos; Raúl Hidalgo (Surveys in Geophysics, 2015)

Dynamics of diffuse carbon dioxide emissions from Cumbre Vieja volcano, La Palma, Canary Islands - Eleazar Padrón; Nemesio M. Pérez; Fátima Rodríguez; Gladys Melián; Pedro A. Hernández; Hirochika Sumino; Germán Padilla; José Barrancos; Samara Dionis; Kenji Notsu; David Calvo (Bulletin of Volcanology, 2015)

Do experimental units of different scale affect the biological performance of European sea bass Dicentrarchus labrax larvae? - K. Lika; M. Pavlidis; N. Mitrizakis; A. Samaras; N. Papandroulakis (Journal of Fish Biology, 2015)
The effects of different tank volumes (2000, 500 and 40 l) on European sea bass Dicentrarchus labrax larval rearing, relating to growth, survival, quality and stress variables, were investigated. A dynamic energy budget ( DEB ) model was used to analyse the results. The hydrodynamics of the tanks exhibited differences, with the water currents in the 2000 l tanks to be almost one order of magnitude stronger than those in the 40 l ones. Important differences in fish growth were observed between small and large tank‐rearing volumes, with the smallest tank resulting in the slowest growth. Based on the DEB model analysis, growth differences were related to feeding rates, with growth in the smaller tank limited by food availability. Differences in survival rates were not statistically significant among the tank‐rearing volumes. The quality evaluation of the fry (in terms of swimbladder, jaw and skeletal abnormalities) showed differences, with the smallest tank having the highest percentage of deformed individuals. This could be attributed to both the feeding variances and the hydrodynamics in the tanks. No differences were observed in terms of whole‐body cortisol at the two developmental stages; flexion, and when the larvae body was fully covered by melanophores; when analysis was performed. This indicates that the allostatic load exerted on fish of different groups was similar and inside the fish‐coping abilities range, in terms of the cortisol response axis. The selection of the experimental scale is of importance, especially when the results are to be transferred and applied on an industrial scale.

Utilization of Phosphogypsum in Tannery Sludge Stabilization and Evaluation of the Radiological Impact - E. Pantazopoulou; O. Zebiliadou; F. Noli; M. Mitrakas; P. Samaras; A. Zouboulis (Bulletin of Environmental Contamination and Toxicology, 2015)

Diffuse volcanic gas emission and thermal energy release from the summit crater of Pico do Fogo, Cape Verde - Samara M. Dionis; Gladys Melián; Fátima Rodríguez; Pedro A. Hernández; Eleazar Padrón; Nemesio M. Pérez; Jose Barrancos; Germán Padilla; Hirochika Sumino; Paulo Fernandes; Zuleyka Bandomo; Sónia Silva; et al. (Bulletin of Volcanology, 2015)

Anomalous Diffuse CO2 Emissions at the Masaya Volcano (Nicaragua) Related to Seismic-Volcanic Unrest - Germán D. Padilla; Pedro A. Hernández; Nemesio M. Pérez; Ernesto Pereda; Eleazar Padrón; Gladys Melián; José Barrancos; Fátima Rodríguez; Samara Dionis; David Calvo; Martha Herrera; Wilfried Strauch; et al. (Pure and Applied Geophysics, 2014)

Aurora B kinase in Hodgkin lymphoma: immunohistochemical pattern of expression in neoplastic Hodgkin and Reed-Sternberg cells - M. Ioannou; E. Kouvaras; E. Stathakis; M. Samara; G. K. Koukoulis (Journal of Molecular Histology, 2014)

Organic and elemental carbon associated to PM10 and PM2.5 at urban sites of northern Greece - Constantini Samara; Dimitra Voutsa; Athanasios Kouras; Kostas Eleftheriadis; Thomas Maggos; D. Saraga; M. Petrakakis (Environmental Science and Pollution Research, 2014)

Amoeba host‐ L egionella synchronization of amino acid auxotrophy and its role in bacterial adaptation and pathogenic evolution - Christopher T. D. Price; Ashley M. Richards; Juanita E. Von Dwingelo; Hala A. Samara; Yousef Abu Kwaik (Environmental Microbiology, 2014)
Summary L egionella pneumophila , the causative agent of L egionnaires' disease, invades and proliferates within a diverse range of free‐living amoeba in the environment, but upon transmission to humans, the bacteria hijack alveolar macrophages. Intracellular proliferation of L . pneumophila in two evolutionarily distant hosts is facilitated by bacterial exploitation of conserved host processes that are targeted by bacterial protein effectors injected into the host cell. A key aspect of microbe–host interaction is microbial extraction of nutrients from the host, but understanding of this is still limited. AnkB functions as a nutritional virulence factor and promotes host proteasomal degradation of polyubiquitinated proteins generating gratuitous levels of limiting host cellular amino acids. L egionella pneumophila is auxotrophic for several amino acids including cysteine, which is a metabolically preferred source of carbon and energy during intracellular proliferation, but is limiting in both amoebae and humans. We propose that synchronization of bacterial amino acids auxotrophy with the host is a driving force in pathogenic evolution and nutritional adaptation of L . pneumophila and other intracellular bacteria to life within the host cell. Understanding microbial strategies of nutrient generation and acquisition in the host will provide novel antimicrobial strategies to disrupt pathogen access to essential sources of carbon and energy.

Concentrations and source apportionment of PM10 and associated elemental and ionic species in a lignite-burning power generation area of southern Greece - G. Argyropoulos; Th. Grigoratos; M. Voutsinas; C. Samara (Environmental Science and Pollution Research, 2013)

Improvement of growth and nitrogen utilization in sheep using sugar beet pulp treated with Trichoderma reesei or urea - Aly B. Okab; Mostafa A. Ayoub; Emad M. Samara; Khalid A. Abdoun; Ahmed A. Al-Haidary; Ahmed A. Koriem; Ayman A. Hassan (Tropical Animal Health and Production, 2012)

Phylogeography of Asian wild rice, Oryza rufipogon : a genome‐wide view - PU HUANG; JEANMAIRE MOLINA; JONATHAN M. FLOWERS; SAMARA RUBINSTEIN; SCOTT A. JACKSON; MICHAEL D. PURUGGANAN; BARBARA A. SCHAAL (Molecular Ecology, 2012)
Asian wild rice ( Oryza rufipogon ) that ranges widely across the eastern and southern part of Asia is recognized as the direct ancestor of cultivated Asian rice ( O. sativa ). Studies of the geographic structure of O. rufipogon , based on chloroplast and low‐copy nuclear markers, reveal a possible phylogeographic signal of subdivision in O. rufipogon . However, this signal of geographic differentiation is not consistently observed among different markers and studies, with often conflicting results. To more precisely characterize the phylogeography of O. rufipogon populations, a genome‐wide survey of unlinked markers, intensively sampled from across the entire range of O. rufipogon is critical. In this study, we surveyed sequence variation at 42 genome‐wide sequence tagged sites (STS) in 108 O. rufipogon accessions from throughout the native range of the species. Using Bayesian clustering, principal component analysis and amova , we conclude that there are two genetically distinct O. rufipogon groups, Ruf‐I and Ruf‐II. The two groups exhibit a clinal variation pattern generally from north‐east to south‐west. Different from many earlier studies, Ruf‐I, which is found mainly in China and the Indochinese Peninsula, shows genetic similarity with one major cultivated rice variety, O. satvia indica , whereas Ruf‐II, mainly from South Asia and the Indochinese Peninsula, is not found to be closely related to cultivated rice varieties. The other major cultivated rice variety, O. sativa japonica , is not found to be similar to either O. rufipogon groups. Our results support the hypothesis of a single origin of the domesticated O. sativa in China. The possible role of palaeoclimate, introgression and migration–drift balance in creating this clinal variation pattern is also discussed.

Migration, isolation and hybridization in island crop populations: the case of Madagascar rice - KRISTIE A. MATHER; JEANMAIRE MOLINA; JONATHAN M. FLOWERS; SAMARA RUBINSTEIN; BRAD L. RAUH; AMY LAWTON‐RAUH; ANA L. CAICEDO; KENNETH L. McNALLY; MICHAEL D. PURUGGANAN (Molecular Ecology, 2010)
Understanding how crop species spread and are introduced to new areas provides insights into the nature of species range expansions. The domesticated species Oryza sativa or Asian rice is one of the key domesticated crop species in the world. The island of Madagascar off the coast of East Africa was one of the last major Old World areas of introduction of rice after the domestication of this crop species and before extensive historical global trade in this crop. Asian rice was introduced in Madagascar from India, the Malay Peninsula and Indonesia approximately 800–1400 years ago. Studies of domestication traits characteristic of the two independently domesticated Asian rice subspecies, indica and tropical japonica , suggest two major waves of migrations into Madagascar. A population genetic analysis of rice in Madagascar using sequence data from 53 gene fragments provided insights into the dynamics of island founder events during the expansion of a crop species’ geographic range and introduction to novel agro‐ecological environments. We observed a significant decrease in genetic diversity in rice from Madagascar when compared to those in Asia, likely the result of a bottleneck on the island. We also found a high frequency of a unique indica type in Madagascar that shows clear population differentiation from most of the sampled Asian landraces, as well as differential exchange of alleles between Asia and Madagascar populations of the tropical japonica subspecies. Finally, despite partial reproductive isolation between japonica and indica , there was evidence of indica/japonica recombination resulting from their hybridization on the island.

Carcinoembryonic antigen promotes tumor cell survival in liver through an IL-10-dependent pathway - J. Milburn. Jessup; R. Samara; P. Battle; L. M. Laguinge (Clinical & Experimental Metastasis, 2005)

A Study of Surface Water Quality in Macedonia, Greece: Speciation of Nitrogen and Phosphorus - D. Voutsa; E. Manoli; C. Samara; M. Sofoniou; I. Stratis (Water, Air, & Soil Pollution, 2001)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)